3t-18=(-45)+6t

Simple and best practice solution for 3t-18=(-45)+6t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t-18=(-45)+6t equation:


Simplifying
3t + -18 = (-45) + 6t

Reorder the terms:
-18 + 3t = (-45) + 6t
-18 + 3t = -45 + 6t

Solving
-18 + 3t = -45 + 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
-18 + 3t + -6t = -45 + 6t + -6t

Combine like terms: 3t + -6t = -3t
-18 + -3t = -45 + 6t + -6t

Combine like terms: 6t + -6t = 0
-18 + -3t = -45 + 0
-18 + -3t = -45

Add '18' to each side of the equation.
-18 + 18 + -3t = -45 + 18

Combine like terms: -18 + 18 = 0
0 + -3t = -45 + 18
-3t = -45 + 18

Combine like terms: -45 + 18 = -27
-3t = -27

Divide each side by '-3'.
t = 9

Simplifying
t = 9

See similar equations:

| 5s-3=5+s | | 5x-7=(2x-2)2 | | 2(x+7)*2=64 | | 5y+3=(2y+5)2 | | (x-2y)2=16 | | -1/3=-5/9a | | (x+2)+(x-3)=x+(x-4) | | 4y+4=3 | | x+10+2x-30+x=180 | | x-(23/4)=-11/12 | | 9.6x=48.96 | | 12+2x=2x+10 | | -4.3v=24.51 | | 3(5x-9)=x-2(6-2x) | | 3(5x-9)=x-2(6-x) | | x/10=0.57 | | 3a^4*6a^2= | | 5(3x-7)+2=7(x+1) | | 2.934=-1.8x | | 4x+x+40+2x=180 | | 8.5=b-(-4) | | 4x-4=(x+3)2 | | 4=4.9-n | | 4x+40+2x=180 | | -0.39=-2.99-n | | -7z^4(-3z^8)= | | -1.5+v=3.08 | | (-w)(-10w^3)= | | 9+7=215 | | x+(-3.4)=-1.3 | | 80x+y=180 | | y+7=y-8 |

Equations solver categories